Inferior vena cava filter usage, complications, and retrieval rate in cancer patients - Abtahian, Farhad; Hawkins, Beau M; Ryan, David P; Cefalo, Philip; Nasser, Nicola J; MacKay, Cheryl; Jaff, Michael R; Weinberg, Ido (The American journal of medicine, 2014)
Venous thromboembolism contributes significantly to morbidity and mortality in cancer patients. Because cancer patients frequently have contraindications to anticoagulation, inferior vena cava filters are commonly placed. The use, safety, and retrieval of retrievable inferior vena cava filters in cancer patients have not been well studied. A retrospective review of retrievable inferior vena cava filter use at a tertiary referral hospital was conducted between January 1, 2009 and December 31, 2011. Indications for inferior vena cava filter placement, anticoagulation practices, complications, filter retrieval, and patient outcomes were analyzed for patients with and without active cancer and for cancer subtypes, including localized and metastatic cases. Of 666 patients receiving retrievable inferior vena cava filters during this time period, 247 (37.1%) had active cancer. Of these, 151 (22.7%) had carcinoma, 92 (13.8%) had sarcoma, and 115 (17.3%) had metastatic disease. Overall, follow-up was available for a median of 401.0 (interquartile range: 107.5-786.5) days. Indwelling filter-related complications occurred in 19.8% of patients without cancer and 17.7% with an active cancer (P = .50). Patients with cancer were less likely to have the filter retrieved (28.0% vs 42.0%, P < .001). In multivariable analysis, cancer was not associated with filter-related complications but was associated with a lower rate of filter retrieval. In a modern cohort of patients undergoing retrievable inferior vena cava filter placement, active diagnosis of cancer is not associated with a significant increase in filter-related complications, but is associated with a reduced rate of filter retrieval.